A tourniquet assisted cardiopulmonary resuscitation augments myocardial perfusion in a porcine model of cardiac arrest. (January 2015) - Yang, Zhengfei; Tang, David; Wu, Xiaobo; Hu, Xianwen; Xu, Jiefeng; Qian, Jie; Yang, Min; Tang, Wanchun
Abstract: Objective: During cardiopulmonary resuscitation (CPR), myocardial blood flow generated by chest compression rarely exceeds 35% of its normal level. Cardiac output generated by chest compression decreases gradually with the prolongation of cardiac arrest and resuscitation. Early studies have demonstrated that myocardial blood flow during CPR is largely dependent on peripheral vascular resistance. In this study, we investigated the effects of chest compression in combination with physical control of peripheral vascular resistance assisted by tourniquets on myocardial blood flow during CPR. Methods: Ventricular fibrillation was induced and untreated for 7 min in ten male domestic pigs weighing between 33 and 37 kg. The animals were then randomized to receive CPR alone or a tourniquet assisted CPR (T-CPR). In the CPR alone group, chest compression was performed by a miniaturized mechanical chest compressor. In the T-CPR group, coincident with the start of resuscitation, the thin elastic tourniquets were wrapped around the four limbs from the distal end to the proximal part. After 2 min of CPR, epinephrine (20 μg/kg) was administered via the femoral vein. After 5 min of CPR, defibrillation was attempted by a single 150 J shock. If resuscitation was not successful, CPR was resumed for 2 min before the next defibrillation. The protocol was continued until successful resuscitation or for a total of 15 min. Five minutes after resuscitation, the elastic tourniquets were removed. The resuscitated animals were observed for 2 h. Results: T-CPR generated significantly greater coronary perfusion pressure, end-tidal carbon dioxide and carotid blood flow. There was no difference in both intrathoracic positive and negative pressures between the two groups. All animals were successfully resuscitated with a single shock in both groups. There were no significant changes in hemodynamics observed in the animals treated in the T-CPR group before-and-after the release of tourniquets at post-resuscitation 5 min. Conclusions: T-CPR improves myocardial and cerebral perfusion during CPR. It may provide a new and convenient method for augmenting myocardial and cerebral blood flow during CPR.